2016
DOI: 10.17235/reed.2016.4086/2015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of delayed cholecystectomy after acute gallstone pancreatitis on recurrence. Consequences of lack of resources

Abstract: Introduction: Acute pancreatitis is often a relapsing condition, particularly when its triggering factor persists. Our goal is to determine the recurrence rate of acute biliary pancreatitis after an initial episode, and the time to relapse, as well as to identify the risk factors for recurrence. Material and method:We included all patients admitted for a first acute gallstone pancreatitis event during four years. Primary endpoints included readmission for recurrence and time to relapse.Results: We included 296… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
2
5
0
Order By: Relevance
“…Our study is the first prospective randomized report one in the literature with long-term follow-up. This confirms, what was found by other non-randomized studies with short follow-up [53] [54] [55] [56] [59], that risk of recurrence is significant in patients with mild acute biliary pancreatitis, without bile duct stones, and in whom cholecystectomy is not performed; thus, an ES is recommended.…”
Section: Discussionsupporting
confidence: 89%
“…Our study is the first prospective randomized report one in the literature with long-term follow-up. This confirms, what was found by other non-randomized studies with short follow-up [53] [54] [55] [56] [59], that risk of recurrence is significant in patients with mild acute biliary pancreatitis, without bile duct stones, and in whom cholecystectomy is not performed; thus, an ES is recommended.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding age, the actual evidence is controversial. Some studies showed no increased risk with age in patients with AP 25,26 . However, these studies were single‐center, retrospective, with few patients, and in the case of Zhang et al 26 .…”
Section: Discussionmentioning
confidence: 98%
“…Some studies showed no increased risk with age in patients with AP. 25 , 26 However, these studies were single‐center, retrospective, with few patients, and in the case of Zhang et al. 26 took into account different etiologies of AP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations